Evaluation of energy sources of an office building - a case study (2019)
The energy building performance depends on the envelope of the building, the installed heating and cooling systems, the heat and cold sources, the interior elements and the control system. By choosing the right concept for a particular building and its operation, a considerable amount of energy and / or investment and operating costs can be saved. The presented work falls within the area of optimization of these systems using the computer simulation method in DesignBuider software. A specific high-rise office building in Brno was considered. The model was verified by comparison with the calculation according to the standard EN ISO 13790. The work focuses mainly on the heating and cooling source variations. The outcome of the work is the evaluation and comparison of several alternatives in terms of heat and cold consumption and economic efficiency.